A re‐examination of the individual differences approach that explains occupational resilience and psychological adjustment among nurses. (9th August 2019) - Heritage, Brody; Rees, Clare S.; Osseiran‐Moisson, Rebecca; Chamberlain, Diane; Cusack, Lynette; Anderson, Judith; Fagence, Anna; Sutton, Katie; Brown, Janie; Terry, Victoria R.; Hemsworth, David; Hegney, Desley G.
Abstract: Aims: This study re‐examines the validity of a model of occupational resilience for use by nursing managers, which focused on an individual differences approach that explained buffering factors against negative outcomes such as burnout for nurses. Background: The International Collaboration of Workforce Resilience model (Rees et al., 2015, Frontiers in Psychology, 6, 73) provided initial evidence of its value as a parsimonious model of resilience, and resilience antecedents and outcomes (e.g., burnout). Whether this model's adequacy was largely sample dependent, or a valid explanation of occupational resilience, has been subsequently un‐examined in the literature to date. To address this question, we re‐examined the model with a larger and an entirely new sample of student nurses. Methods: A sample of nursing students ( n  = 708, Age M ( SD ) = 26.4 (7.7) years), with data examined via a rigorous latent factor structural equation model. Results: The model upheld many of its relationship predictions following further testing. Conclusions: The model was able to explain the individual differences, antecedents, and burnout‐related outcomes, of resilience within a nursing context. Implications for Nursing Management: The results highlight the importance of skills training to develop mindfulness and self‐efficacy among nurses as a means of fostering resilience and positive psychological adjustment.